Validation of modeling the delamination process of composite panels of load-bearing elements of aircraft structures - I. S. Belousov (Космические аппараты и технологии)
Both in the manufacture and operation of structural elements made of layered composite materials, interlayer defects may occur upon impact as a result of operation or violation of manufacturing technology, which significantly reduces the strength characteristics of such structures. Therefore, taking into account the effect of such defects on strength is an urgent task. The main purpose of this work is to present the results of validation of finite element models of the deformation process of structural elements made of layered composites with interlayer defects. Two types of specimens are considered in the work: samples in the form of a strut with a wide through embedded delamination and plates with a round embedded delamination. The embedded delamination was created by adding a thin fluoroplastic film of the required size to the composite package. Compression tests of such specimens were carried out, and data on the growth of interlayer defects were obtained. Finite element models are constructed taking into account the growth of interlayer defects during compression. Using the constructed models, a nonlinear static problem was solved, taking into account the local buckling of the specimen in the defect area and its further post buckling behavior, accompanied by an increase in the interlayer defect. The experimental and calculated data are compared. The influence of interlayer fracture characteristics on the stratification process is shown.